2016
DOI: 10.1038/srep31205
|View full text |Cite|
|
Sign up to set email alerts
|

The Expression of Human Cytomegalovirus MicroRNA MiR-UL148D during Latent Infection in Primary Myeloid Cells Inhibits Activin A-triggered Secretion of IL-6

Abstract: The successful establishment and maintenance of human cytomegalovirus (HCMV) latency is dependent on the expression of a subset of viral genes. Whilst the exact spectrum and functions of these genes are far from clear, inroads have been made for protein-coding genes. In contrast, little is known about the expression of non-coding RNAs. Here we show that HCMV encoded miRNAs are expressed de novo during latent infection of primary myeloid cells. Furthermore, we demonstrate that miR-UL148D, one of the most highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 85 publications
2
82
0
Order By: Relevance
“…Infected monocytes expressed relatively high level of UL138 while showing only trace level of IE1 transcript ( Fig. 2A), thus manifesting the hallmark of latent infection (25,27,28,33,43,44). Our latently infected monocytes release only trace amount of infectious virus, while differentiation of these infected monocytes into dendritic cells resulted in detectable IE expression as well as production of infectious virions ( Fig.…”
Section: Single Cell Transcriptomic Analysis Of Latently Infected Cd1mentioning
confidence: 84%
“…Infected monocytes expressed relatively high level of UL138 while showing only trace level of IE1 transcript ( Fig. 2A), thus manifesting the hallmark of latent infection (25,27,28,33,43,44). Our latently infected monocytes release only trace amount of infectious virus, while differentiation of these infected monocytes into dendritic cells resulted in detectable IE expression as well as production of infectious virions ( Fig.…”
Section: Single Cell Transcriptomic Analysis Of Latently Infected Cd1mentioning
confidence: 84%
“…Therefore, the expression level and potential function of miR-UL148D during HCMV latency could be further studied using in vivo system in the future. Moreover, while this manuscript was under review, Lau et al also reported that miR-UL148D is expressed during latency and demonstrated that miR-UL148D could limit proinflammatory cytokine secretion of latently infected cells by inhibiting ACVR1B expression[73], which suggests that miR-UL148D may exert multiple function to facilitate viral latent infection. The future study could further explore the multiple role of miR-UL148D in the viral latency.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, two fairly newly discovered HCMV miRNAs, miR-US5-1 and miR-UL112-3p, have recently been shown to target members of the IκB kinase (IKK) complex, IKKα and IKKβ, therefore reducing NF-κB signaling during late infection (Hancock et al, 2017) and, consequently, the expression of proinflammatory genes encoding cytokines and chemokines (Liu et al, 2017). The secretion of cytokines and chemokines including IL-6 is further inhibited by miR-UL148D, viral miRNA that has been shown to be predominantly expressed during latency (Lau et al, 2016;Goodwin et al, 2018).…”
Section: Microrna Signaling In Cytomegalovirus Infectionmentioning
confidence: 99%